A waterbomb origami tower for convertible photothermal evaporation. Issue 36 (16th August 2022) - Liu, Xiaojie; Tian, Yanpei; Chen, Fangqi; Mu, Ying; Caratenuto, Andrew; Minus, Marilyn L.; Zheng, Yi
Abstract : A portable waterbomb origami pattern-based tower-like structure, named an "origami tower", works as a convertible photothermal evaporator floating on water for efficient solar-driven interfacial desalination under one sun illumination. Abstract : Configured with a rapid evaporation rate and a high photothermal conversion efficiency, solar-driven interfacial evaporation displays considerable promise for seawater desalination. Inspired by the versatility and deployability of origami-based structures, we demonstrate a portable waterbomb origami pattern-based tower-like structure, named an "origami tower", as a convertible photothermal evaporator floating on water for efficient solar-driven interfacial desalination. The origami tower has predictable deformability, featuring reversible radial expansion and contraction radially accompanied by small changes in the axial direction. The reversible adjustability of the origami tower offers convenience for transportation and storage, while the quick expansion into its tower shape provides rapid deployment capabilities. Benefiting from an enlarged evaporation surface, excellent light trapping ability, and heat localization, the origami-tower photothermal evaporator yields an evaporation rate of 2.67 kg m −2 h −1 under one sun illumination. This reversible 3D origami-based photothermal evaporator opens a new avenue for building a portable and efficient solar thermal desalination system.